Evaluation of Droplet Digital Polymerase Chain Reaction (ddPCR) for the Absolute Quantification of Aspergillus species in the Human Airway - Poh, Tuang Yeow (Int J Mol Sci, 2020)
Background: Prior studies illustrate the presence and clinical importance of detecting Aspergillus species in the airways of patients with chronic respiratory disease. Despite this, a low fungal biomass and the presence of PCR inhibitors limits the usefulness of quantitative PCR (qPCR) for accurate absolute quantification of Aspergillus in specimens from the human airway. Droplet digital PCR (ddPCR) however, presents an alternative methodology allowing higher sensitivity and accuracy of such quantification but remains to be evaluated in head-to-head fashion using specimens from the human airway. Here, we implement a standard duplex TaqMan PCR protocol, and assess if ddPCR is superior in quantifying airway Aspergillus when compared to standard qPCR. Methods: The molecular approaches of qPCR and ddPCR were applied to DNA fungal extracts in n = 20 sputum specimens obtained from non-diseased (n = 4), chronic obstructive pulmonary disease (COPD; n = 8) and non-cystic fibrosis bronchiectasis (n = 8) patients where Aspergillus status was known. DNA was extracted and qPCR and ddPCR performed on all specimens with appropriate controls and head-to-head comparisons performed. Results: Standard qPCR and ddPCR were both able to detect, even at low abundance, Aspergillus species (Aspergillus fumigatus - A. fumigatus and Aspergillus terreus - A. terreus) from specimens known to contain the respective fungi. Importantly, however, ddPCR was superior for the detection of A. terreus particularly when present at very low abundance and demonstrates greater resistance to PCR inhibition compared to qPCR. Conclusion: ddPCR has greater sensitivity for A. terreus detection from respiratory specimens, and is more resistant to PCR inhibition, important attributes considering the importance of A. terreus species in chronic respiratory disease states such as bronchiectasis.